Telaah Maqashid Syariah terhadap Penerapan Sanksi Kebiri Kimia bagi Pelaku Pedofilia - Asrofi Asrofi; Zulfahmi, Zulfahmi; Abdul Haris Nasution (CV. Doki Course and Training, 2025)
Sexual violence against children is a serious crime and requires appropriate and effective sanctions. One form of punishment applied in Indonesia is chemical castration, as stipulated in Law Number 17 of 2016 and Government Regulation Number 70 of 2020. Although it aims to provide a deterrent effect, this punishment has drawn pros and cons, especially regarding its effectiveness and compatibility with the principles of maqashid sharia. Maqashid sharia emphasises the protection of five main aspects: soul, mind, offspring, property, and religion. This study aims to analyse the application of chemical castration sanctions within the framework of maqashid sharia, as well as assess its impact on the rehabilitation of perpetrators and the prevention of paedophilia crimes. A qualitative method was used with a literature study approach collected from various legal sources and maqashid sharia theory. The results of the analysis show that although this sanction is in line with the principles of preventing harm and protecting future generations, its implementation still draws pros and cons. The main criticism states that chemical castration may violate human rights and Islamic principles of justice as a whole, mainly due to the significant psychological and social impact on the offender, as well as its debatable effectiveness as a temporary solution. The study concluded that although chemical castration has the potential to be a preventive measure, there is still a need for in-depth studies and the development of alternative sanctions that emphasise justice for both parties and a proportional rehabilitative approach to overcome trauma and the negative impact of sexual crimes against children.